2019
DOI: 10.1155/2019/3429635
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Testicular Toxicity to Cadmium Exposure Intraperitoneally and Orally

Abstract: The toxic effects of cadmium (Cd) on reproductive parameters are widely described in the literature. Experimental models often make use of the intraperitoneal route (i.p.), although human intoxication occurs preferentially by the oral route and can be continuous. However, little is known about the effect of Cd administration routes on the testicular structure. Thus, this study investigated the testicular impact of Cd exposure comparing both i.p. and oral routes, both single dose (SD), in addition to the oral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 59 publications
5
23
0
4
Order By: Relevance
“…Nitric oxide (NO) in the present study displayed a marked expression; meanwhile CD 68 which is an indicator of macrophages was amplified in group III compared to group I. These results were in accordance with Mouro et al (2019). Oxidative stress is estimated to excite transcription factors, comprising NF‐kB (Bowie & O’Neill, 2000; Bubici, Papa, Dean, & Franzoso, 2006; Kyriakis & Avruch, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Nitric oxide (NO) in the present study displayed a marked expression; meanwhile CD 68 which is an indicator of macrophages was amplified in group III compared to group I. These results were in accordance with Mouro et al (2019). Oxidative stress is estimated to excite transcription factors, comprising NF‐kB (Bowie & O’Neill, 2000; Bubici, Papa, Dean, & Franzoso, 2006; Kyriakis & Avruch, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study has investigated the impact of Cd toxicity in mouse testis by comparing the intraperitoneal (single dose) and oral (single and fractionated dose) routes of administration. However, results showed that the oral route (fractionated dose) of Cd administration has more potential to induce testicular toxicity through increased Cd concentration and decreased SOD and glutathione-s-transferase (GST) activity in testicular tissue (Mouro et al, 2019).…”
Section: Oxidative Toxicitymentioning
confidence: 99%
“…Além de poderem acumular exponencialmente a medida em que vão sendo transmitidas de um animal para outro através da alimentação, escalando a cadeia alimentar através dos diversos níveis tróficos, processo denominado de biomagnificação. Animais carnívoros, como homem, que ocupam posições mais elevadas na cadeia alimentar, são os que possivelmente possuem maior concentrações teciduais de metais (MOURO et al, 2019).…”
unclassified
“…Alterações em parâmetros fisiológicos humanos advinda a exposição a tóxicos ambientais tem sido descrita mundialmente para diversos órgãos e sistemas (NELSON, BUNGE, 1974, MOURO et al,2019. Por exemplo, a concentração espermática humana decresceu cerca de 50-60% entre os anos de 1973 e 2011 em países industrializados como os Estados Unidos, da Europa e a Nova Zelândia (LEVINE et al, 2017).…”
unclassified
See 1 more Smart Citation